Death in the sun: the bioarchaeology of an early post-medieval hospital in Gibraltar. (4th May 2018) - Pomeroy, Emma; Grant, Jennifer; Ward, Devin; Benady, Sam; Reinoso del Río, Ma Cristina; Gutierrez López, José Ma; Mata Almonte, Esperanza; Ramírez León, Jorge; Cobos Rodríguez, Luis; Finlayson, Geraldine; Finlayson, Stewart; Finlayson, Clive; et al.
Abstract : SUMMARY: In 2014, during construction work at the ex-Civil Hospital in Gibraltar, excavations led by the Gibraltar Museum revealed a major, previously unknown burial ground containing more than 200 skeletons . We present the historical, archaeological and radiometric dating evidence from the site alongside the results of initial osteological analyses. The data indicate that the burials pertain to an earlier 16th-century Spanish hospice, and therefore stand to offer new insights into the functioning of this early modern hospital and the health and movements of people at a time of incipient globalization.